Implementation of cascade control for wheeled mobile robot straight path navigation - Ng, K. H. (IEEE, 2012)
A cascade controller was proposed for mobile robot navigation because of the simplicity of control algorithm. For a robot that requires to only complete straight path navigation, the cascade controller is an attractive solution. Compared to typical mobile robot navigation algorithms, this cascade control does not need any path tracking control and only uses simple PID for navigation. For each mobile robot wheels, a position PID controller is cascaded to a velocity PID controller. An additional PID controller is added in between both wheels to make sure the mobile robot moves in a straight path. An experiment was done on a differential drive robot and results were presented.